An Integrated Study of Parent Satisfaction with Ongoing Home Visitation for Moms and Children - Myhydeen, Yousif Mufaz (Journal of Biology and Life Science, 2023)
The present study focuses on an integrated study of parent satisfaction with ongoing home visitation for moms and children. This paper aims to integrate and critically examine the available research on parent satisfaction with ongoing home-visiting care for mothers and children. Study selection, data extraction, data synthesis, and critical assessment were all carried out by two separate researchers. The results showed that 13 studies (nine quantitative and four qualitative) passed the inclusion criteria. This research indicated that as compared to parents who got regular or institutional care, those who received home visiting treatments reported much better levels of satisfaction. Parental happiness was shown to be influenced by the quantity of services received. The effects on parents’ happiness, however, were contradictory. The nurse-client connection, respect, autonomy, and emotional support were also identified as crucial components of care by parents. Conclusion: Delivering services in the context of excellent and empowered relationships is just as crucial as ensuring that home-visiting practitioners offer evidence-based care and treatments. It is advised that further study be conducted to better comprehend the care process and the processes that improve parent satisfaction and positive experiences, hence maximizing the quality of care provided.